Loyalitas Pelanggan Hotel Generasi Z di Seminyak, Bali: Peran Customer Relationship Management, Social Media Engagement, dan Trust - Mahaditha, Putu Rio Satria; Sihombing, Irene Hanna H; Darmawijaya, I Gede (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of Customer Relationship Management and Social Media Engagement on Generation Z customer loyalty, with Trust as a mediating variable in hotels located in Seminyak, Bali. The research employed an explanatory quantitative approach with purposive sampling, involving 400 Generation Z respondents who had stayed at least once in Seminyak hotels within the last 12 months. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that Customer Relationship Management and Social Media Engagement have a positive and significant effect on customer loyalty. Both also significantly influence Trust, which in turn positively affects loyalty. Furthermore, Trust mediates the relationship between Customer Relationship Management and Social Media Engagement with Generation Z customer loyalty. These findings contribute theoretically to tourism marketing and hospitality management studies, particularly regarding the integration of Customer Relationship Management and Social Media Engagement strategies in building loyalty through Trust. The practical implication suggests that hotels in Seminyak should strengthen personalized and interactive service strategies and optimize social media use to foster Trust and sustain emotional relationships with Generation Z customers.